Cytomegalovirus infection in non-immunosuppressed critically ill patients - Manisha Jain; Shalini Duggal; Tulsi Das Chugh (Journal of Infection in Developing Countries)
Cytomegalovirus (CMV) is an important and common cause of mortality and morbidity in immunocompromised patients such as those with HIV/AIDS, transplant recipients on immunosuppressive therapy, and malignant hematological disease. After primary infection with CMV the virus becomes latent in multiple organs and can later be reactivated during severe dysregulation of the immune system. A large population carry dormant virus and are thus at risk for reactivation.